(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service activity was motivated by the limited access to communication experienced by people with hearing impairments in their daily social interactions, which restricts their participation in accessing information and engaging with the wider community. This program aimed to enhance communication accessibility through the implementation of integrated communication technology tailored to the needs of the Gerkatin Malang community. The implementation method consisted of partner needs identification, participatory planning, program implementation, mentoring and empowerment, as well as joint evaluation. The results indicate that the applied technology effectively improved communication effectiveness, expanded access to information, and increased the self-confidence of community members in various social contexts. As a follow-up to these findings, continuous mentoring, optimization of technology utilization by partners, and strengthening collaboration with relevant stakeholders were carried out to ensure program sustainability and potential replication. This activity has a positive impact on improving the quality of social interaction among people with hearing impairments and contributes to the development of an inclusive and disability-friendly society.